Abnormal Tibiofemoral Contact Stress and Its Association With Altered Kinematics After Center-Center Anterior Cruciate Ligament Reconstruction: An In Vitro Study. (April 2013) - Imhauser, Carl; Mauro, Craig; Choi, Daniel; Rosenberg, Eric; Mathew, Stephen; Nguyen, Joseph; Ma, Yan; Wickiewicz, Thomas
Background: Abnormal tibiofemoral contact stress and aberrant kinematics may influence the progression of osteoarthritis in the anterior cruciate ligament (ACL)–deficient and the ACL-reconstructed knee. However, relationships between contact stress and kinematics after ACL reconstruction are poorly understood. Therefore, we posed the following research questions: (1) How do ACL deficiency and reconstruction affect the kinematics of and contact stress in the tibiofemoral joint? (2) What kinematic differences are associated with abnormal contact stress after ACL reconstruction? Hypothesis: Center-center ACL reconstruction will not restore knee kinematics and contact stress. Correlations will exist between abnormal contact stress and aberrant kinematics after ACL reconstruction. Study Design: Controlled laboratory study. Methods: Clinical tests of anterior and rotational stability were simulated on 11 cadaveric knees using an industrial robot. Tests were conducted with the ACL intact, sectioned, and after single-bundle ACL reconstruction using a quadrupled hamstring autograft with tunnels drilled through the center of the native footprints. Kinematics were recorded during the tests. Contact stress was continuously recorded from a stress transducer fixed to the tibial plateau, and mean contact stress was calculated regionally. Results: ACL deficiency resulted in increased mean contact stress in the posterior sectors of the medial and lateral compartments under anterior and rotational loads, respectively. Reconstruction reduced stress in these locations; however, contact stress abnormalities remained. On average, kinematics were overconstrained after ACL reconstruction (≤1.8 mm and ≤2.6° in all directions). However, combinations of overconstrained and underconstrained motions in abduction/adduction and medial-lateral translation in response to combined moments, and anterior-posterior translation, medial-lateral translation, and axial rotation in response to an anterior load were associated with abnormal mean contact stress. Conclusion: ACL reconstruction reduces high stresses generated in the posterior compartment of the ACL-deficient knee. Abnormal contact stress after ACL reconstruction is related to multiplanar variations in knee kinematics. Clinical Relevance: Clinical measures of multiplanar kinematics may help to better characterize the quality of ACL reconstruction. Such measures may help identify patients at increased risk of long-term joint degeneration following this surgery.